(untitled) (Medical Forum Monthly, 2022)
Objective: To explore the public image toward nursing as a profession at private tertiary care hospital of Karachi, Pakistan. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Jinnah Medical College Hospital, Karachi, from November 2020 to February 2021. Materials and Methods: Data was collected by well-designed questionnaires by non-probability consecutive sampling technique from general public coming in hospital except medical staff. Data was evaluated using SPSS version 25. Results: 101 participants took part in the study. About 70% participants think that nursing is a respectful profession. 100% participants believe that nurses play vital role for the caring of the patients. 88.5% participants answered that in future, nursing profession will be well developing in Pakistan. 92.5% participants believe that nurses work for the humanity. 50% participants believe that nurses work independently without doctors. Conclusion: People perception of nursing are strongly influenced by nursing care that they receive. Majority of the participants gave the positive remarks about nursing image and profession.